Incomplete insurance market and its policy implication within European Monetary Union - Jarkko Jääskelä (Bank of Finland, 1997)
The purpose of this discussion paper is to consider consumption insurance and its various channels at the level of the individual and at the level of the economy as a whole in the context of the European Monetary Union.First we introduce a theoretical framework to derive implications of international risksharing and review the empirical work on the subject.We conclude that the efficient pooling of consumption risks is not the feature of real world. Second, we discuss of potential market imperfections and the extent to which the current market structure can offer consumption insurance.Finally, we discuss relevant policy implications of incomplete insurance market.Two arrangements are under consideration: fiscal federalism from the point of view of insurance arrangement and a proposition for opening new risksharing markets.
URN:NBN:fi:bof-20140807367
Keywords: 330; Consumption insurance; capital markets; labor mobility; labor contracts; fiscal federalism; financial innovations